Firm Characteristics and Non-financial information Disclosures of Elite issuers firms in Nigeria Exchange Group - Osemwegie-Ero, Joy Omeghie; Chinedu-Chiejine, Anthonia N.; Erhirhie, Felix Erhinyoja (The Journal of Accounting and Management, 2024)
The study examined the effect of firms’ characteristics on non-financialinformation disclosures of Elite issuers in Nigeria Exchange Group. It used eight (8) Elite Issuers firms as classified by the Nigeria Exchange group for 2021 financial period, spanning a period of ten (10) years (2012-2021), utilizing annual reports obtained from the firms in Nigerian Exchange Group. Panel least square regression model was used to test the perceived effect. The study used simple regression model and employed longitudinal survey research design. Hausman and Heteroskedasticity tests were respectively employed to determine appropriate effect of each variable as well as to ensure the reliability of results. Fixed panel estimator and Panel least regression analysis was employed to examine effect of firms’ characteristics on non-financial information disclosures of the studied firms. The findings revealed that: Elite Firms’ size has negative significant effect on non-financial information disclosures at 5% level of significance, and that firms’ age has positive and significant effect on non- disclosures. The study recommended among others that: Large firms should give reasonable attention to non-financial information disclosures in order to avoid negative spillover and reputational effects associated with inconsistency of non-financial information disclosures, as nondisclosure of nonbinding information poses a risk and speaks loudly against such firms. Therefore, all listed firms in Nigeria Exchange Group are encouraged to engage sincerely in non-financial information disclosures to maximize the antecedent benefits that are linked with non-financial information disclosures practices.